Relationship between high dose intake of vitamin B12 and glaucoma: Evidence from NHANES 2005–2008 among United States adults - Liu, Zhongwei; Hu, Yi; Wang, Yuhan; Xu, Baiwei; Zhao, Jiangyue; Yu, Ziyan (Frontiers in Nutrition, 2023)
Objective Glaucoma has currently become the second leading cause of blindness in the world. Serum vitamin B12 level has been found to be involved in the development and progression of glaucoma. We performed the present study to confirm this association. Methods This cross-sectional study included 594 participants aged 40 years and older in the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2008. Retinal imaging was performed using the Ophthalmic Digital Imaging system (Retinography) to assess the retina for the presence of features of glaucomatous lesions. Logistic regression models were used to assess the association between dietary vitamin intake and glaucoma. Results After screening, 594 subjects were finally included. Among all vitamin intakes, we observed significant differences between the two groups for vitamin B12 intake (5.93 vs. 4.77 mg, p = 0.033). According to the logistic regression results, the intake of vitamin B12 was significantly positively associated with glaucoma (model 1: OR = 1.078, 95% CI = 1.019–1.141; model 2: OR = 1.092, 95% CI = 1.031–1.158; model 3: OR = 1.092, 95% CI = 1.029–1.158). After performing a quantile regression, we observed a significant positive association between vitamin B12 intake and incident glaucoma in the fourth quartile (model 1: OR = 1.133, 95% CI = 1.060–1.210; model 2: OR = 1.141, 95% CI = 1.072–1.215; model 3: OR = 1.146, 95% CI = 1.071–1.226). Conclusions Therefore, the above results, high-dose intake of vitamin B12 may promote the development of glaucoma.